Responding to the commodity boom with varieties of resource nationalism: a political economy explanation for the different routes taken by Africa's new oil producers. Issue 4 (November 2020) - Hickey, Sam; Abdulai, Abdul-Gafaru; Izama, Angelo; Mohan, Giles
Highlights: Provides an original comparative analysis of the different institutional responses made by africa's new oil producers to the challenge of oil governance during the commodity super-cycle. Challenges current framings of 'resource nationalism', which tend to explain this in terms of either 'ideas' or 'institutions', and argues for an alternative theoretical perspective that locates the role of both institutions and ideas within an analysis of politics and power relations. Argues that the incentives and ideas that characterise a country's 'political settlement' offers a more compelling explanation for the varieties of resource nationalism that emerged to the commodity boom in the first decade of the century. Shows that the extent of resource nationalism differed both between ghana and uganda and within ghana over time (depending on which political party was in power). This is evidenced by an analysis of the deal-making process between government and international oil companies and the political management of bureaucratic enclaves. Abstract: The institutional responses of Africa's new producers to the early 21st century commodity boom differed both between and within countries over time. Despite making similarly sized discoveries in the mid-2000s, Ghana and Uganda took different routes, with Ghana oscillating between a neoliberal modality and a soft version of resource nationalism (depending on which party was in power), whilst Uganda adopted a more consistent and robust resource nationalist position. Current explanations for varieties of resource governance tend to focus on either institutions or ideas. We argue for an alternative theoretical perspective that locates the entwined role of both institutions and ideas within a deeper analysis of a country's 'political settlement'. This offers a more compelling explanation for the varied responses to the commodity boom in sub-Saharan Africa, and suggests that different types of political settlements have had significant implications for how oil governance has progressed in different contexts.